2020
DOI: 10.3390/ijerph17239041
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Association between Driver’s Age and the Risk of Causing a Road Crash through Mediation Analysis

Abstract: It has been widely reported that younger and older drivers have an excess risk of causing a road crash. Two casual hypotheses may coexist: the riskier driving behaviors and age-related mechanisms in extreme age groups (direct path) and the different environmental and vehicle circumstances (indirect path). Our aim was to quantify, through a mediation analysis, the percentage contribution of both paths. A case-control study was designed from the Spanish Register of Road Crashes with victims from 2014 to 2017. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In addition, in the frequency analysis, the greatest accident happened once the weather was clear, in line with the results of other studies [26,58]. e significant effect of age in reducing accidents has been emphasized in some studies, contrary to the result of this research, indicating that there is less effect of this factor [51,63]. In addition, the results of frequency analysis indicated that most accidents occurred by the driver between the age of 30 and 45, similar to these studies [26,58].…”
Section: Comparison and Discussionsupporting
confidence: 88%
“…In addition, in the frequency analysis, the greatest accident happened once the weather was clear, in line with the results of other studies [26,58]. e significant effect of age in reducing accidents has been emphasized in some studies, contrary to the result of this research, indicating that there is less effect of this factor [51,63]. In addition, the results of frequency analysis indicated that most accidents occurred by the driver between the age of 30 and 45, similar to these studies [26,58].…”
Section: Comparison and Discussionsupporting
confidence: 88%
“…We should be cautious, however, in assuming a direct causal path between age and risky decision making without considering other factors such as experience, vehicle type or the environment. Indeed, age has a major influence on risky driving and the level of involvement in road collisions for the majority of young drivers, even when controlling for environment and type of vehicle [ 9 ]. However, the effect of experience should not be underestimated as it has been found to influence risk estimation and decision making independently of age [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that youth and inexperience is responsible for crashes in a significant proportion of young drivers [ 6 ]. Some of these crashes are due to a lack of fully developed skills (such as hazard perception; [ 7 , 8 ]), though other crashes are due to risky driving behaviours [ 9 ]. The willingness of a driver to engage in risky driving behaviour depends on their perception of the danger involved in performing such actions (risk estimation) and the perceived reward vs. costs that may be gained (e.g., peer respect, arriving sooner at a destination).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, older vehicles are less likely to have safety features. Safety equipment and its defects cause a crash and may increase its intensity [ 42 ].…”
Section: Resultsmentioning
confidence: 99%